Official development assistance to the West African Subregion: Do the trade war and economic policy uncertainties in the US and China Matter? - Chinwe Okoyeuzu; Ebere Ume Kalu (Research in Globalization, 2022)
This work was set to investigate empirically the possible impact of economic policy uncertainties as well the trade conflict between China and the US on the Official Development Assistance to the West African Sub-region. From the bivariate test for linear association, we found a co-movement of the War with ODA. This implies that aids can increase even as the war goes on as such aids may be used as a penetration strategy for trade and other economic purposes. It was also found that there is a greater sensitivity of ODA to US uncertainty than the Chinese Uncertainty. The error correction model shows that it is obvious that Official Development Aids adjust to the shocks and dynamics of the raging economic uncertainties and trade war between China and the US.
Keywords: 330; ODA; Economic Policy Uncertainty; Trade War; West Africa; The US and China